2004
DOI: 10.1103/physrevd.69.063506
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological variation of the deuteron binding energy, strong interaction, and quark masses from big bang nucleosynthesis

Abstract: We use big bang nucleosynthesis calculations and light element abundance data to constrain the relative variation of the deuteron binding energy since the Universe was a few minutes old, ␦QϭQ(BBN) ϪQ(present). Two approaches are used, first treating the baryon to photon ratio as a free parameter, but with the additional freedom of varying ␦Q, and second using the WMAP value of and solving only for ␦Q.Including varying Q yields a better fit to the observational data than imposing the present day value, rectifyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
162
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(168 citation statements)
references
References 49 publications
6
162
0
Order By: Relevance
“…), and of the way the world would be once those thresholds are crossed (e.g., how does a neutron-stable world behave? ), as the masses are tuned via variations in w. The changes in w contemplated here-which lead to altogether qualitatively different worlds-are larger than those studied in the context of observational constraints on time or space variations in w or other Standard Model parameters in our universe (e.g., [21,22,23,24,25,26,27,28,29,30,31].) In addition this paper is does not actually apply anthropic reasoning or thoroughly explore the parameter space of possible worlds (e.g., [32]); it just explores the nuclear astrophysics of varying w with other parameters held fixed.…”
Section: Introductionmentioning
confidence: 93%
“…), and of the way the world would be once those thresholds are crossed (e.g., how does a neutron-stable world behave? ), as the masses are tuned via variations in w. The changes in w contemplated here-which lead to altogether qualitatively different worlds-are larger than those studied in the context of observational constraints on time or space variations in w or other Standard Model parameters in our universe (e.g., [21,22,23,24,25,26,27,28,29,30,31].) In addition this paper is does not actually apply anthropic reasoning or thoroughly explore the parameter space of possible worlds (e.g., [32]); it just explores the nuclear astrophysics of varying w with other parameters held fixed.…”
Section: Introductionmentioning
confidence: 93%
“…In order to make such a connection, we make use of previous analyses relating the deuterium binding energy B D to fundamental constants. Using a potential model, the dependence of B D on the nucleon, σ-meson and ω-meson has been estimated (Flambaum & Shuryak 2002;Dmitriev & Flambaum 2003;Flambaum & Shuryak 2003;Dmitriev et al 2004;Coc et al 2007;Damour & Donoghue 2008). Furthermore, using the quark matrix elements for the nucleon, variations in B D can be related to variations in the light quark masses (particularly the strange quark) and thus to the corresponding quark Yukawa couplings and Higgs vev, v. The remaining sensitivity of B D to a dimensionful quantity is ascribed to the QCD scale Λ.…”
Section: Using the Deuterium Binding Energy As A Linkmentioning
confidence: 99%
“…δ NN is used as a free parameter. The dependence of the deuterium binding energy on δ NN then offers us the possibility of relating this parameter to the gauge and Yukawa couplings if one matches this prediction to a potential model via the σ and ω meson masses (Flambaum & Shuryak 2003;Dmitriev et al 2004;Coc et al 2007;Damour & Donoghue 2008) or the pion mass, as suggested by Yoo & Scherrer (2003); Epelbaum et al (2003); Beane & Savage (2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the inclusion of varying B d (as in FIG. 1) changes these abundances dramatically, indicating the important role of the deuteron binding energy in BBN [7,8,18].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…These effects separately cannot solve the whole inconsistency and a combination of them is needed, e.g. [17] (there are also works which use a single quantity to account for the inconsistency, such as a varying deuteron binding energy [18] and the Brans-Dicke cosmology with a varying Λ term [61]). But from a theoretical viewpoint, such combinations may not be necessary since, as mentioned in the introduction, the variation of one fundamental constant will often be accompanied by the variations of some other constants; these changes together would play the role of several effects combined.…”
Section: Numerical Resultsmentioning
confidence: 99%